Properties of Recycled Polycarbonate/Waste Silk and Cotton Fiber Polymer Composites - KOÇAK, EMİNE DİLARA; USTA, İSMAİL; TAŞDEMİR, MÜNİR (TAYLOR & FRANCIS AS, 2008)
Polymer-based composite structures have advantages over many other materials. The most important advantage is the higher mechanical properties obtained from the composites when supported by fiber reinforcement. The mechanical and thermal properties of fiber-reinforced composite structures are affected by the amount of fibers in the structures, orientation of the fibers and fiber length. Silk and cotton fibers are used in many fields but especially in clothing and textiles. However, there is not enough research on their usage as reinforcement fibers in composite structures. Silk fibers as a textile material have better physical and mechanical properties than other animal fibers. The improvement of the mechanical and physical properties of the composite structures allows them to be used in many areas. From economical, technological and environmental points of view, the improvement of mechanical and physical properties of polymeric materials are receiving much attention in recent studies. In this study, different application areas were chosen to evaluate the waste silk and waste cotton rather than classic textile applications. Waste silk and cotton and recycled polycarbonate polymer were mixed and as a result composite structures were obtained. Silk and cotton waste fiber dimensions were in between 1 mm, 2.5 mm and 5 mm. The recycled PC/silk and cotton wastes were mixed in the rates of 97%/3%. Mixtures were prepared by twin-screw extruder. Tensile strength, % elongation, yield strength, elasticity modulus, Izod impact strength, melt flow index (MFI), heat deflection temperature (HDT) and Vicat softening temperature properties were determined. To determine the materials' thermal transition and microstructure properties, differential scanning calorimetry (DSC) and scanning electron microscopy (SEM) were used.
Keywords: polymer composite; recycled polycarbonate; waste cotton; waste silk; MECHANICAL-PROPERTIES; COMMON THERMOPLASTICS; CELLULOSIC FILLERS; COUPLING AGENTS; PROCESSING AIDS; METHACRYLAMIDE; POLYPROPYLENE; EFFICIENCY